(untitled) (Update Dental College Journal, 2020)
The aim of this comparative study was to evaluate the effectiveness of auto polymerized acrylic denture on oral mucosa. The total 40 partially edentulous patients were included in this study and randomly divided into two groups. Group A consisted of 20 patients and group B consisted of 20 patients who were attending in the Department of Prosthodontics and they were treated by auto polymerized and heat cure acrylic denture respectively. Follow up was done after 1 weeks and 4 weeks of insertion of denture. Data were recorded by using predesigned data collection sheet and analyzed by using SPSS. In case of autopolymerized acrylic denture, after 4 weeks of treatment most of the cases showed oral mucosal changes which could be turned to malignancy (p<0.5). But in case of heat cure acrylic denture satisfactory mucosal changes were not found. However, heat cure acrylic denture did not show any statistically significant difference (p>0.5). So it can be concluded that there is a direct adverse reaction between autopolymerized acrylic denture and oral mucosa. Update Dent. Coll. j: 2020; 10 (2): 18-20